My love mix-up! Vol. 6 - Hinekure, Wataru; Cash, Jan Mitsuko (Shojo beat manga., 2023)
"Aoki has a crush on Hashimoto, the girl in the seat next to him in class. But he despairs when he borrows her eraser and sees she's written the name of another boy--Ida--on it. To make matters more confusing, Ida sees Aoki holding that very eraser and thinks Aoki has a crush on him. Aoki is dating Ida, a boy in his class. In order to buy Ida a birthday present, Aoki started working part-time, but now it seems Ida doesn't want Aoki to spend his hard-earned money on him. What's a boyfriend to do?"--